2022
DOI: 10.1038/s41536-022-00210-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization reveals time- and dose-dependent inflammatory cytokine-mediated regulation of human stem cell derived T-cell development

Abstract: The generation of T-cells from stem cells in vitro could provide an alternative source of cells for immunotherapies. T-cell development from hematopoietic stem and progenitor cells (HSPCs) is tightly regulated through Notch pathway activation by Delta-like (DL) ligands 1 and 4. Other molecules, such as stem cell factor (SCF) and interleukin (IL)-7, play a supportive role in regulating the survival, differentiation, and proliferation of developing T-cells. Numerous other signaling molecules influence T-lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…These data show that thymic cells from female and male donors show significant differences in gene expression. Given that higher levels of cytokine signaling has been previously shown to influence thymus and T cell biology 44,45 , our data suggests male and female T cells develop in different signaling environments and may respond differently to cytokine stimuli. This suggests that biological sex should be included as a variable in studies on immune cell and thymic organoid screening models as a critical parameter affecting cell growth, differentiation, and function.…”
Section: Spatial Multiomic Profiling Of Human Postnatal Thymus Identi...mentioning
confidence: 68%
See 1 more Smart Citation
“…These data show that thymic cells from female and male donors show significant differences in gene expression. Given that higher levels of cytokine signaling has been previously shown to influence thymus and T cell biology 44,45 , our data suggests male and female T cells develop in different signaling environments and may respond differently to cytokine stimuli. This suggests that biological sex should be included as a variable in studies on immune cell and thymic organoid screening models as a critical parameter affecting cell growth, differentiation, and function.…”
Section: Spatial Multiomic Profiling Of Human Postnatal Thymus Identi...mentioning
confidence: 68%
“…We first analysed the ability of the four Notch ligands present in the thymus to induce T-lineage commitment or alternative lineage development from cord-blood derived CD34 + hematopoietic stem and progenitor cells (HSPCs) in a defined, feeder-free culture system 44 (Figure 2H). We included titrated concentrations of granulocyte-macrophage colony-stimulating factor (GM-CSF), which is produced by mast cells at the CMJ, and has been shown previously to support development of DCs 51 .…”
Section: Jag1 Drives Early Thymic Progenitor Development Towards Thym...mentioning
confidence: 99%
“…It is worth noting that while the process yielded a mixture of CD34 + and CD34cells, no enrichment or purification for CD34 + CD45 + target cells was required for further differentiation. Indeed, we found that by separation of the free-floating progenitor cells from the main EB we were able to generate lymphoid progenitor cells that co-expressed CD5 and CD7 marking their T cell commitment 49,50 . Continued differentiation of the lymphoid progenitor cells resulted in CD4 and CD8 DP T cells again, without enrichment of the starting population.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors: Other factors found to have an influence on T cell lymphopoiesis include IL-7, SCF, IL-3, IL-15, CXCL12 and TNFa. While IL-3 alone appears to stimulate myeloid-biased differentiation, when paired with TNFa there appears to be a strong proliferative effect towards lymphoid-biased differentiation [ 351 ]. CXCL12 (which binds CXCR4) has been found to be expressed on TECs [ 352 ], and promotes Notch-dependent differentiation [ 353 ].…”
Section: In Vitro Differentiation Into Lymphoid Cellsmentioning
confidence: 99%